Analysis of packaging defect on goat milk caramel candy in Etawa Agroprima - Yahyono, Khansa Aulia Arinda Putri Ari; Hidayah, Nurul (Journal of Halal Science and Research, 2023)
Goat's milk has the same benefits as cow's milk. Goat's milk contains many nutrients, especially complete protein from all kinds of essential amino acids. Etawa Agroprima is a company engaged in the processing and marketing dairy products. One of the products produced is goat's milk caramel candy. These candies are packaged using candy wrappers and diamond paper, which is covered with paper again, then put into PE plastic, sealed using a sealer, and put in a cardboard box. This packaging is intended to maintain the quality of the candy because the candy is easily runny if left open so that the caramel candy is not easily damaged. Writing this final project aims to determine the types of defects that occur in caramel candy products, the number of defective products for the entire product, and the causes of product defects—analysis of product types and defects using Pareto diagram analysis, while the cause using fishbone diagram analysis. Analysis of the data obtained on Etawa Agroprima using the two diagrams shows that the results of the Pareto diagram analysis show three types of defects, including torn packaging 75.56%, damaged packaging 13.33%, and no expiration label 11.11%. Then from the fishbone diagram analysis, it can be seen that the main factor causing defects in goat's milk caramel candy products is the packaging factor. Some root causes include manual production and packaging work, not using modern packaging equipment, contamination by physical contact, etc. Therefore, it is necessary to use automatic packaging tools.